Idiomatic Expression in Movie Screenplay Entitled Beauty and The Beast - Udianti, Ni Kadek; Istri Aryani, I Gusti Agung; Sumaryana Putra, I Komang (Udayana Journal of Social Sciences and Humanities, 2020)
This study entitled Idiomatic Expression in Movie Screenplay Entitled “Beauty and The Beast”. This study is aimed at classifying the types of phrasal verb idioms and analyzing the meaning of each phrasal verb idiom encountered in Beauty and The Beast screenplay. The data were taken from the movie screenplay written by Stephen Chbosky and Spiliotopoulus entitled Beauty and The Beast. The data were collected using the documentation method by applying the note-taking technique. In the analysis, this study used the qualitative method, and narrative method used to present the data analysis. In analyzing types of idioms, the writer divided phrasal verb idiom enchanted into six types and explained each pattern. In analyzing the meaning of each phrasal verb idiom, the writer described the literal meaning of an individual word and then explained the idiomatic meaning appropriate with the dialogue. The result of the analysis showed that the dominant pattern used among phrasal verb idioms enchanted in Beauty and The Beast is the combination between intransitive + adverb and the least of all patterns is the combination of transitive + adverb + preposition. Furthermore, the most type of meaning found is transparent, where mostly, the meaning of phrasal verb idioms in the screenplay, and the meaning of their literal word are similar.